The Influence of Cultural Factors on Global Marketing Strategies: A Comprehensive Review - Wuryantini, Aris (Penelitian dan Pengembangan Ilmu, 2024)
Cultural factors play an important role in influencing marketing strategies and consumer behavior in international markets. This article examines four key elements—cultural values, social norms, consumer habits, and cultural symbols—and how each of them shapes an effective marketing approach. Cultural values ​​such as collectivism versus individualism, power distance, and uncertainty avoidance influence consumer preferences and appropriate marketing strategies across cultures. Social norms determine acceptable behavior in a society, guiding how products are marketed and received. Consumer habits, influenced by customs and traditions, influence product design, pricing, and promotion. Cultural symbols such as color, language, and iconography play an important role in marketing communications and brand perception. By understanding and adapting marketing strategies to these cultural factors, companies can increase their marketing effectiveness and build stronger connections with global audiences.